Penciptaan Tari Manggala Kridha sebagai Media Pembentukan Karakter bagi Anak - Supriyanti Supriyanti; D. Suharto (Journal of Urban Society's Arts, 2015)
enciptaan tari anak ini didasarkan dari rasa keprihatinan ketika melihat prosespembelajaran tari anak dengan materi ajar kurang sesuai dengan dunia bermain anakanak.Berbagaikasus privattari anak atau lomba tari tingkat prasekolah dasar seringdijumpaipenggunaan materi tari orang remaja.Keberadaanekspresiseni pentingbagipembentukan karakter sejak dini, sehingga anak mampu mengembangkan idekreatifdan inovatifyang bersifat kritis dan produktif.Esensi pendidikan menarimenyangkutaspek kognitif,afektif,dan psikomotorik. Formatkoreografianaktentuharusmempertimbangkantingkat usia, terutamatingkat kematangan emosidanketerampilannya agar tari itu mampu membentuk kualitas kepribadiananak.Prosespenciptaan TariManggalaKridha dengan tema memfokuskan pada figurprajuritsebagai orang yang memiliki keberanian dan kepatuhan dalam menjalankantugasnegara sehingga ketika mati dalam pertempurania menjadi seorang pahlawan.Idegarapan TariManggalaKridha diilhami dari sosok keberanian dan kepatuhanseorangprajurit pembela bangsa dan negara.Secarasimbolis, gerak-gerak yangdisusunsebenarnya merupakandialog gerak sepertisikap dan gerak langkah tegap, menyerang,gerak menangkis, gerak menghindar.Musiktari dalam komposisi tariini bersumber pada karawitan tradisi gaya Yogyakartayang dikembangkan menurut kebutuhangarapan tari dengan berbagai macam interpretasigarap permainan.Tarian inidapat ditarikan oleh pria maupun wanita. Penariberjumlah ganjil 11 - 15 orangataukelompok terdiridari anak-anak usia 4-6 tahun, yaitu usia anak yang hidupdalamdunia bermain.The Dance Creation of Manggala Kridha as the Revealing Media of the Character Building for Children. The research on the creation of children dance is based on a big concern while seeing the learning process of children dances with inappropriate teaching materials in accordance to the realm of children’s play. A variety cases of found in children dance private course or dance competitions in the pre-elementary school level is commonly found for which the purpose of dance materials is addressed to teenagers. Therefore, the presence of the art expression is necessary for building the character since childhood, so children can develop their creative and innovative idea critically and productively. The essence of dance education involves the aspects of cognitive, affective, and psychomotorics. The format of children choreography should obviously consider the age level of participants, particularly the level of emotional and skill maturity so that the dance itself can build the quality of children’s personality. The creation process of Manggala Kridha dance with its theme mainly focuses on the soldier figure as person which has bravery and compliance in doing the nation task, so as he died in the battle he becomes a hero. The creation idea of Manggala Kridha dance is mainly inspired by a braving and compliance figure. Symbolically, the created movements are basically as movement dialogues like the firm attitude and sturdy steps, attaching, parrying, and eschewing. The source of dance music for the children dance composition of “Manggala Kridha” is the traditional gamelan of Yogyakarta which is developed based on the needs of dance composition with sort of its interpretation. This dance can be performed either by man or woman. Particularly, the dancers might be odd numbers, more or less around 11-15 dancers or groups consisting of a 4 to 6-year old children, who are still in the realm of children’s play.